أثر المحاسبة الخلاقة على قرارات المستثمر في ظل تفاوت كفاءة السوق: دراسة حالة على عينة من المستثمرين في سوق العراق للأوراق المالية - علي إبراهيم حسين (PROSPECTIVE RESEARCHES, 2023)
Accounting plays a significant role in markets in general and particularly in the stock markets, sinceit serves investment decisions through the accounting data which it provide concerning the stance of companies in these markets and according to which investments and financial analysts decisions are made. So any manipulated or miseaoling data will be negatively reflected on the process of investment, as a result, there has to be some precautionary measures because some crippled companies administrations resort to manipulate the published accounting figures for the purpose of showing unreal image of the company in an attempt to influence investment decisions in away that better serves their personal interests. Many legal and illegal accounting measures are used to perform this kind of fraud through taking advantage of the flexibility to apply acceptable accounting principles, accounting measures and policies which can be used to adjust financial bills in away conforming to the company’s administration objectives. This process is called the creative accounting. The impact of this sort of accounting on investors decisions mainly relies on the market efficiency on the one hand and on the investor’s education and on his degree of reliance on the financial analysts on the other hand. Creative accounting is mainly found in inefficient markets rather than efficient ones, but its impact on investment decisions will surge with increasing market efficiency and will decline with dwindling market efficiency.